Mortality Inequality in Canada and the United States: Divergent or Convergent Trends? - Baker, Michael; Currie, Janet; Schwandt, Hannes (Journal of Labor Economics, 2019)
Mortality is a crucial indicator of well-being, and recent mortality trends have been a subject of public debate in many Western countries. This paper compares mortality inequality in Canada and the United States over the period 1990/91 through 2010/11. In Canada, mortality inequality remained constant among the youngest but increased for men over 24 and women over 14. In contrast, in the United States, mortality inequality fell for children and youth and either modestly increased or held steady at older ages. By 2010/11, the initially higher US rates of infant and child mortality had almost converged to their Canadian counterparts.